2014
DOI: 10.1007/s11426-014-5212-x
|View full text |Cite
|
Sign up to set email alerts
|

Dicyanovinyl-unit-induced absorption enhancement of iridium(III) complexes in long-wavelength range and potential application in dye-sensitized solar cells

Abstract: Iridium complexes with dicyanovinyl-grafted phenylpyridine/1-phenylisoquinoline as ligands are synthesized and their photophysical, electrochemical, and sensitization properties in DSSCs are investigated. The iridium complexes present significantly enhanced absorption from 400 to 525 nm. The 1-phenylisoquinoline-based iridium complex show bathochromic-shift emission in DMSO solution compared with their phenylpyridine-based counterpart, while their absorption response and photoluminescence peak in solid show li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The localization of the frontier molecular orbitals enabling the charge transfer directionality from the cyclometalated fragment to the “anchoring” ligand (necessary for binding a dye to the semiconductor surface) is also very important. So, the introduction of the dicyanovinyl 38 or bulky coumarin chromophore fragments 39 into the cyclometalated ligands, although producing strongly visible light-absorbing complexes, gave rise to the unfavorable localization of the orbitals which, in turn, resulted in low efficiencies of DSSCs. The use of chromophore-appended ancillary ligands, for example, bis(arylimino)acenaphthenes afforded panchromic iridium( iii ) complexes, 40 but functionalization of these ligands by “anchoring” carboxy-groups was accompanied by a dramatic drop of the absorption efficiency in the visible spectral range 41 or by irreversible oxidation of the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The localization of the frontier molecular orbitals enabling the charge transfer directionality from the cyclometalated fragment to the “anchoring” ligand (necessary for binding a dye to the semiconductor surface) is also very important. So, the introduction of the dicyanovinyl 38 or bulky coumarin chromophore fragments 39 into the cyclometalated ligands, although producing strongly visible light-absorbing complexes, gave rise to the unfavorable localization of the orbitals which, in turn, resulted in low efficiencies of DSSCs. The use of chromophore-appended ancillary ligands, for example, bis(arylimino)acenaphthenes afforded panchromic iridium( iii ) complexes, 40 but functionalization of these ligands by “anchoring” carboxy-groups was accompanied by a dramatic drop of the absorption efficiency in the visible spectral range 41 or by irreversible oxidation of the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…DSSCs were fabricated according our published procedures [18]. The electrolyte for all the cells contained 0.6 M 1-butyl-3-methyl imidazolium iodide (BMII), 0.03 M I 2 , 0.02 M LiI, 0.10 M guanidinium thiocyanate, and 0.5 M 4-tert-butylpyridine in a mixture of acetonitrile and valeronitrile (volume ratio 85:15).…”
Section: The Preparation and Measurement Of Dsscsmentioning
confidence: 99%
“…Just recently, we demonstrated that introducing of dicyanovinyl (DCV) moiety into Ir III bis(phenylpyridinato)picolinate (HIr(ppy) 2 pic), resulting in complex 1 (shown in Scheme 1), could be used as an efficient means to extend absorption response towards longer wavelengths [17]. Furthermore, the derivative of the complex 1 with carboxyl acid anchoring group (complex 2, shown in Scheme 1) was developed to use for DSSCs [18]. Unfortunately, the cells based on complex 2 present unanticipated poor performance parameters (only 0.19% energy conversion efficiency).…”
Section: Introductionmentioning
confidence: 99%